Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1002/ccd.20451
|View full text |Cite
|
Sign up to set email alerts
|

Randomized comparison of operator radiation exposure during coronary angiography and intervention by radial or femoral approach

Abstract: Controversial data have been published on the amount of radiation exposure during radial coronary procedures. We hypothesized that in the current era, high-volume operators with optimal technique would not be exposed to higher radiation doses during radial procedures. A total of 297 patients undergoing cardiac catheterization (195 elective diagnostic coronary angiograms and 102 elective coronary interventions) were prospectively assigned in a random fashion to the radial access (RA) or femoral access (FA). All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
57
4
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(69 citation statements)
references
References 36 publications
5
57
4
3
Order By: Relevance
“…In our study, significantly high fluoroscopy time of r-CA and r-PCI groups is consistent with previous studies (9,21,22). It may be argued that mean fluoroscopy time of f-CA as well as r-CA is relatively high.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our study, significantly high fluoroscopy time of r-CA and r-PCI groups is consistent with previous studies (9,21,22). It may be argued that mean fluoroscopy time of f-CA as well as r-CA is relatively high.…”
Section: Discussionsupporting
confidence: 92%
“…But, Rao et al (27) (from the National Cardiovascular Data Registry) also reported higher fluoroscopy time in r-PCI group as compared to f-PCI group (13.5 vs 11.3 min; p<0.01). Moreover, Lange et al (9) demonstrated 50 % increase in radiation exposure with radial approach despite the non-significant difference in fluoroscopy time among r-PCI and f-PCI groups. This shows the diversity in available data and demands further randomized, blinded studies in larger cohorts.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Adicionalmente, a análise de uma escala subjetiva do grau de dificuldade nos leva na mesma direção. Isso se explica por ser esse um estudo de curva de aprendizagem, ou seja, a falta de experiência do operador no acesso transradial tem papel maior na extensão do procedimento e no tempo de exposição aos raios X 22 . Preocupações quanto ao aumento da exposição à radiação nos operadores primários podem ser diminuídas pelo posicionamento do braço junto do paciente e pelo uso de campos de proteção de chumbo com movimentação livre e suporte superior.…”
Section: Discussionunclassified
“…It also saves the time of busy catheterization laboratories by reducing occupancy and hence increases the number of procedures. It also helps reducing the radiation exposure that often considered trivial but in fact a worrisome problem (14,15).Nature believes in diversity and hence in this way it maintains the beauty and continuity in life. Variety is a blessing and it often gives us a way out from a trapped situation.…”
mentioning
confidence: 99%